Recommendations From the International Consensus Conference on Anemia Management in Surgical Patients (ICCAMS). Issue 4 (21st April 2023) - Shander, Aryeh; Corwin, Howard L.; Meier, Jens; Auerbach, Michael; Bisbe, Elvira; Blitz, Jeanna; Erhard, Jochen; Faraoni, David; Farmer, Shannon L.; Frank, Steven M.; Girelli, Domenico; Hall, Tiffany; et al.
Abstract : Abstract : Background: Perioperative anemia has been associated with increased risk of red blood cell transfusion and increased morbidity and mortality after surgery. The optimal approach to the diagnosis and management of perioperative anemia is not fully established. Objective: To develop consensus recommendations for anemia management in surgical patients. Methods: An international expert panel reviewed the current evidence and developed recommendations using modified RAND Delphi methodology. Results: The panel recommends that all patients except those undergoing minor procedures be screened for anemia before surgery. Appropriate therapy for anemia should be guided by an accurate diagnosis of the etiology. The need to proceed with surgery in some patients with anemia is expected to persist. However, early identification and effective treatment of anemia has the potential to reduce the risks associated with surgery and improve clinical outcomes. As with preoperative anemia, postoperative anemia should be treated in the perioperative period. Conclusions: Early identification and effective treatment of anemia has the potential to improve clinical outcomes in surgical patients.